ANALISIS HUKUM BISNIS TERHADAP UNDANG-UNDANG CIPTA KERJA DALAM INDUSTRI KELAPA SAWIT (Sengketa Perizinan Pasca Implementasi OSS-RBA) - Olyhabana Situmorang; Martono Anggusti; Jinner Sidauruk (Jurnal Syntax Transformation, 2025)
The palm oil industry is a strategic sector for the Indonesian economy, but in practice it often faces various problems, particularly related to licensing, which triggers conflicts. In response, the government passed the Job Creation Law, which introduced the Online Single Submission Risk-Based Approach (OSS-RBA) system to simplify regulations and accelerate the licensing process. This study aims to conduct a legal business analysis of the implementation of the Job Creation Law and its impact on licensing disputes in the palm oil industry following the implementation of OSS-RBA. Using a legal research approach, the analysis focuses on the gap between legal norms and their implementation in practice. The results of the study show that although the OSS-RBA is normatively intended to provide legal certainty and efficiency, in reality, the implementation of this system has actually led to new licensing disputes. The main problems identified include a lack of data synchronization between the central and regional governments, inadequate facilities and infrastructure, and insufficient human resources. Furthermore, this system is considered to weaken environmental control instruments and minimize public participation, as evidenced in cases where the participation of indigenous peoples is merely symbolic. This creates a gap between the administrative legitimacy obtained through the system and the socio-legal reality in the field. It is concluded that the effectiveness of the Job Creation Law in resolving disputes is highly dependent on strong implementation support. Therefore, comprehensive institutional reform is needed, including strengthening data interoperability across agencies, establishing a unified oversight body, and harmonizing central-regional regulations. This reform must be grounded in the spirit of achieving substantial justice that balances economic rights with social and environmental responsibilities, not merely procedural efficiency.